2022
DOI: 10.1101/2022.11.10.515805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allele surfing causes maladaptation in a Pacific salmon of conservation concern

Abstract: The Anthropocene threatens worldwide biodiversity, with a potential to induce species decline and range contraction. In this context, it is important to quantify species adaptive potential and how demographic changes may impact selection efficacy and the burden of deleterious mutations in different populations. Here we show that key evolutionary processes, including variation in effective population size through postglacial change in demography and recombination rates have affected the efficacy of selection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…This pattern was, however, not observed for all types of deleterious mutations, which suggests that selection has been as efficient at removing deleterious alleles for all these categories. Overall, the depletion of minor alleles in recolonized populations goes against what has been reported in the literature (Peischl et al, 2013;Henn et al, 2016;Rougemont et al, 2023). However, this could be explained because the continental populations were recolonized long ago and are not at the extremities of range expansion anymore.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…This pattern was, however, not observed for all types of deleterious mutations, which suggests that selection has been as efficient at removing deleterious alleles for all these categories. Overall, the depletion of minor alleles in recolonized populations goes against what has been reported in the literature (Peischl et al, 2013;Henn et al, 2016;Rougemont et al, 2023). However, this could be explained because the continental populations were recolonized long ago and are not at the extremities of range expansion anymore.…”
Section: Discussionmentioning
confidence: 45%
“…Like most recolonization events in other species, the recolonization of Europe by the barn owl probably occurred with bottlenecks at the front of the colonization side, followed by population expansion (Ursenbacher et al, 2015;McDevitt et al, 2022). This scenario has been shown to lead to an increased number in deleterious mutations per individual and a reduction in selection efficiency due to the smaller effective population size both with simulated data (Peischl et al, 2013) and with empirical data such as out-of-Africa human expansion (Henn et al, 2016;McCoy and Akey, 2016) and salmons postglacial recolonization (Rougemont et al, 2023).…”
Section: Introductionmentioning
confidence: 94%
“…More specifically, outside of an unlikely model of additive dominance, the masking advantage provided by whole genome duplication when mutations are partially or fully recessive results in an accumulation of deleterious mutations that in turn leads to a protracted drop in the fitness of polyploids with tetrasomic inheritance during expansion relative to their diploid counterparts. Indeed, recent evidence in Coho salmon ( Oncorhynchus kisutch ) showed residual tetraploid regions of their genome that had not yet re-diploidized harbored a greater mutational load than the diploidized regions (Rougemont et al 2023)…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, outside of an unlikely model of additive dominance, the masking advantage provided by whole genome duplication when mutations are partially or fully recessive results in an accumulation of deleterious mutations that in turn leads to a protracted drop in the fitness of polyploids with tetrasomic inheritance during expansion relative to their diploid counterparts. Indeed, recent evidence in Coho salmon (Oncorhynchus kisutch) showed residual tetraploid regions of their genome that had not yet re-diploidized harbored a greater mutational load than the diploidized regions (Rougemont et al 2023) Abundant evidence has demonstrated a link between polyploidy and previously glaciated areas (Brochmann et al 2004;Paun et al 2006;Novikova et al 2018;Sutherland and Galloway 2018;Rice et al 2019;David 2022;Booker et al 2023). While support for this observation has many adaptive explanations-such as fixed heterozygosity (Stebbins 1985;Brochmann et al 2004), increased adaptability of gene regulatory networks (Freeling and Thomas 2006;Hegarty and Hiscock 2007;Fusco et al 2010;Yao et al 2019;Ebadi et al 2023), or the relaxed constraint on gene duplicates enabling more rapid adaptation (Lynch and Conery 2000;Lynch and Force 2000;Gout and Lynch 2015)-these arguments too rely on some level of subgenomic differentiation, and therefore disomy, to maintain their validity.…”
Section: The Genetic Consequences Of Range Expansion In Polyploidsmentioning
confidence: 99%
“…Understanding why we observe these genetic groups is important (e.g., (Nadeau et al 2016;Rougemont et al 2023)). Are they a technical artifact from trying to cluster genomes influenced by isolation-by-distance?…”
Section: Influences On the Population Structure Of Fraser River Salmonmentioning
confidence: 99%